Primary oral mucosal melanoma: case report - Carla Aguiar Andrade; Cláudia Cardoso de Macedo Oliveira; Eduardo Vinícius Mendes Roncada; Diogo Gonçalves Ribeiro (Sociedade Brasileira de Dermatologia (SBD), 2021)
Oral mucosa melanoma (OMM) represents 0.2% to 8% of melanoma cases. It mainly affects the palate and gums of patients between 40 and 70 years old. It is initially asymptomatic, contributing to late diagnosis and poor prognosis. The treatment of choice consists of surgical resection, and adjuvant radiotherapy and chemotherapy may be used. We report a case in an 80-year-old male patient with primary gingival and hard palate melanoma who underwent tumor resection followed by palate reconstruction. We emphasize the importance of a complete physical examination and active search for lesions in the oral mucosa for early diagnosis.